Executive Committee Minutes 2013-08-22 - Academic Senate:::::::::
Approval of Agenda. Minutes delayed. President Report. Provost Report. Statewide Senate Report. Vice Chair Report. Vice President of Administration and Finance Report. Chief Student Affairs Officer Report. Associated Students Report. Recommendation from the DRB re: Timely return of assignments referred to SAC and FSAC. Member of Executive Committee appointed to the Sustainability Executive Committee – J. Mahdavi. Chancellor White's Visit to SSU on October 9th. Faculty Eligible to Emeritus Status – approved for Senate consent calendar. Discussion of how to celebrate 50 years of the Senate. Senate Agenda – approved.